Shakespeare in the Arab World - Hennessey, Katherine (2019)
Offering a variety of perspectives on the history and role of Arab Shakespeare translation, production, adaptation and criticism, this volume explores both international and locally focused Arab/ic appropriations of Shakespeare’s plays and sonnets. In addition to Egyptian and Palestinian theatre, the contributors to this collection examine everything from an Omani performance in Qatar and an Upper Egyptian television series to the origin of the sonnets to an English-language novel about the Lebanese civil war. Addressing materials produced in several languages from literary Arabic (fuṣḥā) and Egyptian colloquial Arabic (‘ammiyya) to Swedish and French, these scholars and translators vary in discipline and origin, and together exhibit the diversity and vibrancy of this field.